Effects of the composition of insects and mammals membranes on the non-specific action of GABAergic insecticides - Asis Rodriguez, Marcos Alberto (2022)
Fluralaner and Fipronil are gabaergic insecticides belonging to the non-competitive antagonists NCA-I and NCA-II families, respectively. While fipronil binds to the pore of the insect homopentameric GABAA receptor (RDL), fluralaner targets a site located in the transmembrane region, at the receptor subunits interface. There is a major interest in the development of highly selective insecticides that are not toxic to vertebrates. In this context, it is interesting the fact that, unlike mammal membranes, which are mainly composed of phosphatidylcholine (PC) lipids, sphingolipids and sterols; insects cannot synthesize sterols. Therefore, they modulate membrane fluidity through the modification of the PC/phosphatidylethanolamine (PE) lipids ratio. This variation in the composition of the membrane of vertebrates and insects could be relevant when we analyze the nonspecific effects of lipophilic compounds on the structure and dynamics of the membrane and ultimately of RDL. Due to the lipophilicity of these compounds, and the location of the receptor binding site for fluralaner, it is probable that these insecticides could reach their binding site through the lipid bilayer. We performed Free diffusion MD simulations of POPC bilayers with increasing concentrations of Cholesterol (CHOL) or POPE, in the absence and in presence of fluralaner or fipronil. Fluralaner and fipronil acted differentially in membranes with the same composition. The analysis of these trajectories showed that fluralaner has a marked effect on the physical properties of binary bilayers containing POPE, and a negligible effect on bilayers containing CHOL. The opposite is true in the case of fipronil. On the other hand, both, fluralaner and fipronil, reduced the CHOL flip-flop rates, except for the POPC-CHOL 1:1 system in which fipronil enhanced it considerably. Our results suggest that fipronil and fluralaner may impact differentially on the physical properties of both types of membranes.